Role of Saliva in Esophageal Defense: Implications in Patients With Nonerosive Reflux Disease. (May 2015) - Yandrapu, Harathi; Marcinkiewicz, Marek; Poplawski, Cezary; Han, Kyung; Zbroch, Tomasz; Goldin, George; Sarosiek, Irene; Namiot, Zbigniew; Sarosiek, Jerzy
Abstract: Background: It has been previously demonstrated that patients with reflux esophagitis exhibit a significant impairment in the secretion of salivary protective components versus controls. However, the secretion of salivary protective factors in patients with nonerosive reflux disease (NERD) is not explored. The authors therefore studied the secretion of salivary volume, pH, bicarbonate, nonbicarbonate glycoconjugate, protein, epidermal growth factor (EGF), transforming growth factor alpha (TGF-α) and prostaglandin E2 in patients with NERD and compared with the corresponding values in controls (CTRL). Methods: Salivary secretion was collected during basal condition, mastication and intraesophageal mechanical (tubing, balloon) and chemical (initial saline, acid, acid/pepsin, final saline) stimulations, respectively, mimicking the natural gastroesophageal reflux. Results: Salivary volume, protein and TGF-α outputs in patients with NERD were significantly higher than CTRL during intraesophageal mechanical ( P < 0.05) and chemical stimulations ( P < 0.05). Salivary bicarbonate was significantly higher in NERD than CTRL group during intraesophageal stimulation with both acid/pepsin ( P < 0.05) and saline ( P < 0.01). Salivary glycoconjugate secretion was significantly higher in the NERD group than the CTRL group during chewing ( P < 0.05), mechanical ( P < 0.05) and chemical stimulation ( P < 0.01). Salivary EGF secretion was higher in patients with NERD during mechanical stimulation ( P < 0.05). Conclusions: Patients with NERD demonstrated a significantly stronger salivary secretory response in terms of volume, bicarbonate, glycoconjugate, protein, EGF and TGF-α than asymptomatic controls. This enhanced salivary esophagoprotection is potentially mediating resistance to the development of endoscopic mucosal changes by gastroesophageal reflux.